Relationship between alcohol craving dimensions and features of comorbid mental health in an alcohol dependent sample. (January 2022) - Cheng, Brandon; Coates, Jason M.; Gullo, Matthew J.; Feeney, Gerald F.X.; Kavanagh, David J.; Young, Ross McD.; Connor, Jason P.
Highlights: Alcohol Use Disorder severity did not strongly predict negative affect or craving. Higher stress was associated with stronger craving. Anxiety independently predicted craving imagery. Younger people had greater craving intensity and imagery. Results may guide future interventions designed to reduce alcohol craving. Abstract: Background and aims: Negative affect and alcohol craving are common features of Alcohol Use Disorder (AUD). Both independently contribute to AUD severity and poorer treatment outcomes, but their relationship is poorly understood. Multidimensional alcohol craving measures now allow for examination of key dimensions of craving. This study explored the relationship between depression, anxiety, stress, and the alcohol craving dimensions of intensity, imagery and intrusiveness. Method: Five-hundred and twenty-five treatment seeking AUD patients (mean age of 39.79 years, SD  = 11.57 years, 67% male) completed the Depression Anxiety Stress Scales (DASS), Alcohol Use Disorder Identification Test-Consumption items (AUDIT-C), and Alcohol Craving Experience (ACE-F) questionnaire, which measured the frequency of craving intensity, imagery and intrusiveness. Regression models predicted main effects of predictors and moderation by alcohol consumption. Results: Higher levels of stress were independently associated with increased craving intensity, imagery and intrusiveness . Significant positive associations were also found between anxiety and craving imagery . The association between depression and craving was not significant after controlling for other predictors. Conclusions: AUD patients experienced higher cravings when stressed and greater imagery when anxious. These results support the need to consider the relationships between stress and craving when managing alcohol dependence.